A Novel Long Noncoding RNA lincRNA00892 Activates CD4+ T Cells in Systemic Lupus Erythematosus by Regulating CD40L - Liu, Xiao; Lin, Jinran; Wu, Hao; Wang, Yilun; Xie, Lin; Wu, Jinfeng; Qin, Haihong; Xu, Jinhua (Frontiers in Pharmacology, 2021)
Objective: The mechanism of CD4+ T-cell dysfunction in systemic lupus erythematosus (SLE) has not been fully understood. Increasing evidence show that long noncoding RNAs (lncRNAs) can regulate immune responses and take part in some autoimmune diseases, while little is known about the lncRNA expression and function in CD4+ T of SLE. Here, we aimed to detect the expression profile of lncRNAs in lupus CD4+ T cells and explore the mechanism that how lincRNA00892 in CD4+ T cells is involved in the pathogenesis of SLE. Methods: The expression profiles of lncRNAs and mRNAs in CD4+ T cells from SLE patients and healthy controls were detected by microarray. LincRNA00892 and CD40L were chosen for validation by quantitative real-time PCR (qRT-PCR). Coexpression network was conducted to predict the potential target genes of lincRNA00892. Then lincRNA00892 was overexpressed in normal CD4+ T cells via lentivirus transfection. The expression of lincRNA00892 was detected by qRT-PCR. The expression of CD40L was detected by qRT-PCR, western blotting, and flow cytometry, respectively. The expression of CD69 and CD23 was measured by flow cytometry. The secretion of IgG was determined by enzyme-linked immunosorbent assay (ELISA). The proteins targeted by lincRNA00892 were measured by RNA pulldown and subsequent mass spectrometry (MS). The interaction between heterogeneous nuclear ribonucleoprotein K (hnRNP K) and lincRNA00892 or CD40L was detected by RNA immunoprecipitation (RIP) assay. Results: A total of 1887 lncRNAs and 3375 mRNAs were found to be aberrantly expressed in CD4+ T cells of SLE patients compared to healthy controls. LincRNA00892 and CD40L were confirmed to be upregulated in CD4+ T cells of SLE patients by qRT-PCR. The lncRNA–mRNA coexpression network analysis indicated that CD40L was a potential target of lincRNA00892. Overexpression of lincRNA00892 enhanced CD40L protein levels while exerting little influence on CD40L mRNA levels in CD4+ T cells. In addition, lincRNA00892 could induce the activation of CD4+ T cells. Furthermore, lincRNA00892 led to the activation of B cells and subsequent secretion of IgG in a CD4+ T-cell–dependent manner. Finally, hnRNP K was found to be among the proteins pulled down by lincRNA00892, and hnRNP K could bind to lincRNA00892 or CD40L directly. Conclusion: Our results showed that the lncRNA expression profile was altered in CD4+ T cells of SLE. LincRNA00892 possibly contributed to the pathogenesis of SLE by targeting hnRNP K and subsequently upregulating CD40L expression to activate CD4+ T and B cells. These provided us a potential target for further mechanistic studies of SLE pathogenesis.